HUBUNGAN PERKAWINAN “Sirang So Sirang”(Pisah tidak Pisah) Pada Keluarga Etnis Batak Toba Kristen Di Kandis Kota Kabupaten Siak - Daniel Ostega Siahaan; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Kandis City of Siak Regency with the aim to obtain information about Marriage Relationship